Usability Testing Kualitas Desain UI Pemahaman Literasi Digital Anak-Anak - Virdyra Tasril; Muhammad Iqbal; Adinda Silvana Dewi; Endicha Eklis Syahputra; Anwar Suhut (Bulletin of Computer Science Research, 2023)
In 2023, digital literacy has increased to be discussed which navigates human interaction with the current digital environment. The purpose of this study is to determine the relationship between digital literacy and user interface (UI) design quality using a usability testing approach. The study involved collecting data through a series of trials with participants representing different levels of digital literacy. The main focus of this study was to assess the extent to which the UI design could improve the digital literacy understanding of the users, namely school children. The parameters evaluated involved aspects of digital literacy, such as the ability to understand and evaluate digital information, as well as usability elements such as interface clarity, navigation efficiency, and user engagement level. The approach used is the design thinking method which focuses on the end result only. Usability testing is an important evaluation method in measuring the effectiveness, efficiency, and user satisfaction of a user interface (UI). This research focuses on the use of usability testing to assess the quality of UI design in the context of understanding digital literacy. The results of this study can provide insight into how the level of digital literacy can affect the user experience in using digital applications and contribute to the development of UIs that are more user-friendly and accessible to various levels of society.